Formulation of Form Gel Peel Off Mask from Ethanol Extract of Hibiscus Rosa-Sinensis L. Leaves - Intana Merdeka Sari; Nur Mahdi; Raisha Hamiddani Syaiful (DSM Publisher, 2025)
Cosmetics made from synthetic materials can cause side effects and damage the natural shape of the skin. One of the cosmetics that can repair, care for facial skin, cleanse and moisturize the skin is a peel-off gel face mask. Hibiscus leaves have the potential to be antibacterial containing flavonoids, saponins and polyphenols. This study aims to determine the optimal formulation of a peel-off gel mask preparation of ethanol extract of Hibiscus leaves (Hibiscus rosa-sinensis L) with concentrations of 40%, 60% and 80%. The method used is the Experimental method. The results of the evaluation test of the physical properties of the peel-off gel mask preparation showed that all formulas met the requirements for a good peel-off gel mask. Analysis of research data with one way ANOVA produced a pH test sig. 0.168> 0.05, a spread power test sig. 0.392> 0.05 showed no significant difference in each formula group while in the adhesion test sig. 0.000 < 0.05, drying time test 0.008 < 0.05, viscosity test 0.010 < 0.05 showed significant differences in each formula group. The peel-off gel mask formula of hibiscus leaf ethanol extract (Hibiscus rosa-sinensis L) which has the most optimal physical properties of the preparation is a formula with a concentration of 80%.